Pragmatic meaning of Mejikuhibiniu’s color acronym illustrating shifting emotional dynamics throughout evolving expressions of love. - Auliya Ruliani Putri Pambareb; Okta Rossydah Ramadhani; Diva Mutiara Nur Aryana; Marlina Angelica Artanti (Universitas Negeri Surabaya, 2025)
Abstract The phenomenon of the change in meaning in a popular song increasingly shows that the symbol in a language is no longer static, but changes following the social context and the emotion from the speaker. The term of “Mejikuhibiniu” at first is an educative acronym for helping the children memories and knowing the color sequence of rainbow, in “Mejikuhibiniu” song by Tenxi experience the pragmatic transformation becoming a metaphor of a love journey that having a complex and full of conflict. This research goal is for showing the meaning of pragmatic,implicature, assumption, and also the strategy of speech acts that emerge from the use of the color symbol in the lyrics. By using a qualitative approach to pragmatic discourse analysis, this research uses Yule’s context theory, Grice’s implicature, Leech’s principles of politeness, Searle's speech acts, and Karttunen's assumptions in analyzing data in the form of official lyrics. The results of this research show that “Mejikuhibiniu” functions as an emotional marker that represents a shift in relationships from happiness into betrayal and emotional breakdown. In addition, found implicatures of jealousy and manipulation, assumptions of exclusive relationships, speech acts expressive based on emotion intentions, also strategy of color metaphor that smooth and sharpen the critic speaker to the conflict of love. Thus, this study confirms that the changes of symbols and culture in popular music show pragmatic dynamics that influence the social growth and psychologic modern speaker. Keywords: Pragmatics, Implicature, Metaphor, Color Symbolism, Emotional Dynamics, Popular Culture. Abstrak Fenomena perubahan dalam makna musik populer menunjukkan adanya simbol-simbol bahasa yang semakin tidak lagi statis, namun berubahnya makna dengan mengikuti konteks sosial dan emosional penuturnya. Istilah yang awalnya adalah akronim edukatif yang digunakan anak-anak untuk membantu mengenali dan menghafal urutan warna pelangi adalah “Mejikuhibiniu”, akan tetapi dalam lagu “Mejikuhibiniu” karya Tenxi mengalami transformasi pragmatik yang berubah menjadi metafora perjalanan cinta yang kompleks dan penuh konflik. Penelitian ini bertujuan untuk mengungkap makna pragmatik, implikatur, praanggapan, dan juga strategi tindak tutur yang ada dari penggunaan simbol warna dalam lirik lagu tersebut. Dengan pendekatan kualitatif analisis wacana pragmatik, penelitian ini menggunakan teori konteks Yule, implikatur Grice, prinsip kesantunan Leech, tindak tutur Searle, dan praanggapan Karttunen untuk menganalisis data berupa lirik lagu ini. Hasil dari penelitian ini menunjukkan bahwa “Mejikuhibiniu” berfungsi sebagai penanda emosional yang merepresentasikan pergeseran hubungan dari kebahagiaan menjadi pengkhianatan dan kehancuran. Dengan tambahan, ditemukan implikatur kecemburuan dan manipulasi, praanggapan eksklusivitas dalam hubungan, tindak tutur ekspresif berbasis intensitas emosi, dan juga strategi metafora warna yang memperhalus sekaligus mempertajam kritik penutur terhadap konflik cinta yang terjadi. Dengan demikian, penelitian ini menegaskan bahwa adanya perubahan fungsi simbol budaya dalam musik populer mencerminkan dinamika pragmatik yang dapat dipengaruhi perkembangan sosial dan psikologis penutur modern. Kata Kunci: Pragmatik, Implikatur, Metafora, simbolisme warna,Dinamika Emosional, Budaya populer.